The Development of Scratch Based Interactive Mathematics Learning Media “Zuma Function” to Enhance Understanding in Relations and Functions - Sari, Merisa Ammelia; Sudihartinih, Eyus; Usdiyana, Dian; Elisya, Nur; Nurhidayat, Indra (FKIP Universitas Lampung, 2024)
Objective: This study aims to describe the process of developing educational multimedia, specifically the “Zuma Function” game, using Scratch programming for mathematics learning on the topic of relations and functions. Methods: The research employed a Research and Development (R&D) approach, following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved 35 mathematics education students from a university in West Java and 6 eighth-grade students from a junior high school in Bandung, Indonesia. Data were collected using various instruments, including questionnaires, tests, interviews, and documentation. Findings: The developed learning media was evaluated by experts, receiving a material expert test score of 81%, and a learning media expert test score of 83%, both categorized as feasible. The functionality test, measured through User Acceptance Testing, yielded an average score of 85.1%, indicating a very feasible category, while the effectiveness test showed a 30.5% improvement in students’ conceptual understanding, with scores rising from 64.83 to 95.33. Conclusion: Based on the study’s findings, the Scratch-based multimedia for teaching relations and functions in mathematics was successfully developed using the ADDIE model. Positive user feedback and significant improvements in student test scores suggest that this multimedia is effective in enhancing students’ understanding of the concept, though there are areas that could be further refined. Keywords: learning media, mathematics game, function, Scratch, ADDIE.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1410-1427